Efektivitas Sanksi Internasional Dalam Menjaga Perdamaian dan Keamanan Global - Ismatul Maula; Mita Armis; Fitria Qutrul Nada; Budi Ardianto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the effectiveness of international sanctions in maintaining global peace and security. International sanctions have become one of the main tools for the international community to deal with conflicts, threats and violations of global peace and security. However, its effectiveness is still limited among academics and policy makers. This research uses a qualitative approach by analyzing case studies of the implementation of international sanctions by the United Nations (UN) and other regional organizations. Data was collected through literature reviews from various sources such as journals, books and official reports. The research results show that the effectiveness of international sanctions is highly dependent on factors such as the type of sanction, the purpose of the sanction, compliance by the target country, coordination between countries, and the resulting economic and political impacts. Sanctions that are well designed, supported by a solid international community, and consider long-term consequences are likely to be more effective in maintaining global peace and security. This research provides meaning for policy makers to design and implement international sanctions more strategically and comprehensively, as well as increase international cooperation in implementing them. This is important to ensure the effectiveness of sanctions in maintaining global peace and security.